Cytochemical and ultrastructural aspects of aquatic carnivorous plant turions - Płachno, Bartosz J. (Springer Vienna, 2014)
Turions, which are modified shoot apices, are vegetative, dormant overwintering organs produced by perennial aquatic plants. In this study, the turion cytochemistry and ultrastructure of Aldrovanda vesiculosa, Utricularia vulgaris and U. stygia were compared with particular emphasis placed on storage substances. These three aquatic, rootless carnivorous plant species were studied at the end of their winter dormancy. At this stage, the turions of all species had starch as their main storage material. In contrast with A. vesiculosa, Utricularia turions were rich in protein storage vacuoles, and proteins were also accumulated as crystalline inclusions in the nuclei. All examined species accumulated lipid droplets in cells of epidermal glands.